(3GdeONd dOQGSI GdYbjOI GdESdGejI Ydi ePgH Cgd GdSfI hGdLeGYI (B/s - (3GdHQjcGf, EHQGgje Hf eMeO Hf YHO Gddgs 1375-1429 (3gLQjs ((3GdQjGV (B:s (3OGQ GHf Gdbje ddfTQ hGdJhRjY ,s (3GdbGgQI (B:s (3OGQ GHf YaGf ddfTQ hGdJhRjY,s, 2015)
(3cJGH (B"(3GdeONd dOQGSI GdYbjOI GdESdGejI Ydi ePgH Cgd GdSfI hGdLeGYI(B" (3jbOe ebOeI TGedI dOQGSI GdYbjOI GdESdGejI HCSdhH ejSQ hTGedI HWQjbI JSGYO Ydi age CSGSjGJgG hJYejb GdEjeGf GdUMjM, hjTJed Ydi YOI eMGhQ CSGSjI, efgG (B: 1. (3eaghe GdYbjOI GdESdGejI(B-2. (3eUGOQ GdYbjOI GdESdGejI(B-3. (3CQcGf GdEjeGf(B-4. (3GdJhMjO(B-5. (3efgL Cgd GdSfI hGdLeGYI aj GdYbjOI(B-6. (3CSHGH GdGfMQGa Yf GdYbjOI GdUMjMI(B-7. (3GdaQb Hjf GdYbGFO GdUMjMI hGdYbGFO GdHGWdI(B-8. (3CgejI GdYbjOI aj MjGI GdeSde(B.s
(3HHdjhLQGajI (B: (3UaMI (B250-253.s
Keywords: (3YbjOIs -- (3Yde GdcdGes